Influence of saccharose supplementation on neuromuscular excitability (NME) during prolonged heavy exercise - Schiestl, G.; Gastman, U.; Steinacker, J. M.; Lehmann, M. (Medicine & Science in Sports & Exercise, 1997)
The hypothesis that deterioration in neuromuscular function during prolonged heavy exercise is stalled by carbohydrate supplementation was tested. Prolonged exercise consisted of 2 hr of cycling, the first hour at 75% of 4 mM lactate performance and the second at 65%. This was followed by a 30 min rest and then a final ramp test to determine degree of exhaustion. Saccharose (15 g in 0.3 L water) or water alone was supplemented after 30, 60, and 90 min in the two trials. The functioning of the vastus medialis muscle deteriorated in the water-alone supplementation test. Deterioration was completely prevented in the saccharose test. This indicates that deterioration in neuromuscular function during prolonged heavy exercise may be related to a deterioration in energy flux rate dependent on a decrease in glycogen supplies. Implication. The ability to execute exact neuromuscular functions is dependent upon the availability of glycogen. In activities where glycogen is depleted (e.g., in the latter stages of a training session, the end of an extended endurance performance) muscular function (skill) will be altered. At training, activities which depend upon exact muscular function (e.g., skill learning) should be performed before any reduction in glycogen availability occurs. For training and competitions, frequent carbohydrate supplementation is necessary to sustain glycogen levels and thus, contribute to neuromuscular efficiency.